Ministry Of Manpower And Immigration Decree No. 126 Of The Year 2013 Dated 13/4/2013 = وزارة القوى العاملة والهجرة قرار رقم 126 لسنة 2013 بتاريخ 13/4/2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.